Fostering Community Awareness of the Importance of Religiosity to Minimize Conflict and Violence - W Waston; M Muthoifin; Sekar Ayu Aryani; Erham Budi Wiranto; Soleh Amini; Andri Nirwana (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This community service aims to teach the people of Solo about the importance of religiosity in minimising conflict and violence. In the context of Solo's multicultural and multireligious society, conflict and violence often arise as a result of tensions between groups or individuals of different faiths. Through strengthening religiosity, we hold a series of activities such as seminars, workshops, and group discussions to increase understanding of religious values that value peace and tolerance. The active participation of various community groups, including religious leaders, community leaders, and youth, enables a rich exchange of views and a deeper understanding of how religiosity can be the foundation for building a peaceful and harmonious society. Evaluation of activities shows an increased understanding of the importance of religiosity in dealing with conflict and violence. At the end of the project, there was an increase in awareness of the importance of interfaith cooperation and rejection of conflict and violence as a solution to differences of faith. Thus, this dedication is the first step in efforts to build a more tolerant and peaceful society in Solo.